Sustainability considerations in bio-hydrogen from bio-algae with the aid of bio-algae cultivation and harvesting: Critical review - Senthil Rathi B.; Dinesh Aravind V.; Ranjith G.; Kishore V.; Ewe L.S.; Yew W.K.; Baskaran R. (Springer Nature, 2025)
Abstract: Microalgae present an enticing alternative to conventional fossil fuel-dependent technologies for producing hydrogen, offering an intriguing and sustainable energy source. Numerous strains of microalgae are under investigation for their capacity to generate hydrogen, alongside various techniques and breakthroughs being developed to optimize the process. However, significant hurdles must be addressed for commercial viability, including the high manufacturing costs and the necessity for efficient harvesting and sorting methods. This paper delves into several aspects concerning hydrogen synthesis in algae, encompassing microalgae anatomy and physiology, hydrogen synthesis via photosynthesis and dark fermentation, and the integration of microalgal hydrogen synthesis with other renewable energy sources. The potential for microalgal hydrogen generation is considered pivotal in transitioning toward a future reliant on more renewable and sustainable energy sources. This review aims to serve as a valuable resource for researchers, decision-makers, and anyone interested in the advancement of environmentally conscious energy technology. The primary objective of this research paper is to scrutinize the challenges, opportunities, and potential outcomes associated with eco-friendly bio-hydrogen production through algae. It evaluates the current technological hurdles facing bio-hydrogen synthesis from algae. Graphical abstract: (Figure presented.) Highlights: Interest in developing renewable fuels, such as hydrogen from biomass, has surged due to escalating energy demands and the imperative to curtail greenhouse gas emissions. Overview of bio-hydrogen production pathway, reactor designs, and configurations for bio-hydrogen production from bio-algae were explored. Environmental, social sustainability and economic feasibility have been reviewed. Discussion: Will bio-hydrogen from bio-algae be a future renewable energy? Which is the best pathway to produce bio-hydrogen from bio-algae? Regarding greenhouse gas emissions, how does the generation of bio-hydrogen from bio-algae compare to conventional hydrogen production techniques? What difficulties lie in increasing the amount of bio-hydrogen produced by bio-algae to satisfy major energy demands? ? The Author(s) 2024.